2007
DOI: 10.1080/01431160600784259
|View full text |Cite
|
Sign up to set email alerts
|

Land cover classification using multi‐temporal MERIS vegetation indices

Abstract: The spectral, spatial, and temporal resolutions of Envisat's Medium Resolution Imaging Spectrometer (MERIS) data are attractive for regional-to global-scale land cover mapping. Moreover, two novel and operational vegetation indices derived from MERIS data have considerable potential as discriminating variables in land cover classification. Here, the potential of these two vegetation indices (the MERIS global vegetation index (MGVI), MERIS terrestrial chlorophyll index (MTCI)) was evaluated for mapping eleven b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 56 publications
1
17
0
1
Order By: Relevance
“…Inglada (2007), supported by empirical evidence, similarly argued that higher number of geometric image features enhances multi-way characterization of objects that naturally have many different geometric properties. Also, pointed out by Dash et al (2007), the choice of dataset source could help in remedying this hindrance by allowing the reduction in the size of the training set required.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 98%
See 1 more Smart Citation
“…Inglada (2007), supported by empirical evidence, similarly argued that higher number of geometric image features enhances multi-way characterization of objects that naturally have many different geometric properties. Also, pointed out by Dash et al (2007), the choice of dataset source could help in remedying this hindrance by allowing the reduction in the size of the training set required.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 98%
“…At coarser spatial resolutions a study was undertaken to evaluate the discriminatory power of two vegetation indices (the global vegetation index and terrestrial chlorophyll index) obtained from MERIS for general land cover mapping (Dash et al, 2007). Although a moderate level of accuracy was achieved using discriminant analysis method, a repetition of the experiment using an SVM technique revealed that the latter methodology resulted in a 6% gain in overall accuracy.…”
Section: General Land Cover Land Use Tasksmentioning
confidence: 99%
“…In recent years, SVMs classification method was applied in remote sensing image interpretation and achieved good results [10][11][12] . However, there still exists one problem, the huge computation in testing phase caused by the large number of support vectors, which greatly blocks it into practical use.…”
Section: Support Vector Machines Classificationmentioning
confidence: 99%
“…Usually, biomass classification refers to land cover type or forest biomass classification. Land cover classification (Dash et al, 2007) and forest biomass estimation (Wulder et al, 2008) are active research topics in the area of remote sensing.…”
Section: Biomass Classificationmentioning
confidence: 99%